Computational investigation on the antioxidant activities and on the Mpro SARS-CoV-2 non-covalent inhibition of isorhamnetin - Spiegel, Maciej; Ciardullo, Giada; Marino, Tiziana; Russo, Nino (Frontiers in Chemistry, 2023)
In the present work, we have demonstrated the utility of quantum mechanics methods based on density functional theory in predicting the antioxidant properties of the flavonoid isorhamnetin, used in traditional medicine in many countries. In the course of the study we determined the acid-base equilibria in aqueous solution, the possible reaction pathways with the •OOH radical and the corresponding kinetic constants, the complexing capacity of copper ions, and the reduction of these complexes by reducing agents such as superoxide and ascorbic anion. Finally, the inhibition ability of the SARS-CoV-2 main protease enzyme by isorhamnetin was examined by molecular dynamics and docking.